Lessons learned from the participatory development of a framework to actively involve people living with dementia, individuals from their social networks, and healthcare professionals in systematic reviews: the DECIDE-SR study - Mike Rommerskirch-Manietta; Christina Manietta; Anna Louisa Hoffmann-Hoffrichter; Helga Rohra; Lisa Fink; Heidemarie Kelleter; Helga Elisabeth Breimaier; Johanna Möller; Stefanie Oberfeld; Birgit Alpers; Martina Roes (Research Involvement and Engagement)
Abstract Background To date, there is no framework for actively involving people living with dementia, individuals from their social networks and healthcare professionals in systematic reviews (SRs). Additionally, no SRs have been planned or partially carried out with the active involvement of these individuals. For these reasons, a framework and a review protocol for a planned SR were developed as part of the federal-funded DECIDE-SR project, in which the abovementioned groups were actively involved as coresearchers. The purpose of this paper is to provide an overview of the project and to illustrate the lessons learned from conducting active research involving this case example. Methods A framework for actively involving coresearchers in SRs was developed via the synthesis of theoretical and empirical findings from a previous research project. The coresearchers participated in meetings and one workshop, which were planned on the basis of the INVOLVE criteria and the ACTIVE framework model, to test and reflect on the previously developed framework. Additionally, an SR protocol was jointly planned during these meetings, and individual SR steps were conducted (e.g., development of the research question). The lessons learned were drawn from the workshop with the coresearchers, who were clustered using the Engaging with Purpose Patient Engagement Framework (EwPPEF). Results Eight coresearchers were actively involved in 15 meetings and one workshop to test and reflect on the framework. The framework allows coresearchers to individually choose their own level of involvement (where the levels are nonhierarchical), and the individual support needs at each step of an SR are considered. Additionally, an SR protocol was developed together with the research question "What is the effect of hospital treatment provided in one’s own living place on people living with dementia?". The lessons learned provide information on all aspects of the EwPPEF (e.g., cobuilding, impact, and inclusiveness) and include implications for conducting SRs that actively involve the public. Conclusions The framework and the SR protocol can now be used for further tests and to gain initial experience in conducting SRs that actively involve the public. Furthermore, the lessons learned can provide other project groups with important insights into actively planning and conducting SRs.